Analysis of Students' Level of Understanding of Hydrocarbon Concepts Using a Three-Level Diagnostic Multiple-Choice Approach - Marsya Divya Olii; Nurhayati Bialangi; Julhim S Tangio; Mangara Sihaloho; Erga Kurniawati (Jambura Journal of Educational Chemistry, 2025)
This research aims to determine students' conceptual understanding ability of hydrocarbon material using a three-tier multiple-choice diagnostic test instrument. The research was conducted at SMA Negeri 2 Wonosari using a descriptive qualitative approach. The research was carried out in the even semester of the 2024/2025 academic year. The research subjects were the students of class XI B at SMA Negeri 2 Wonosari, with a sample size of 28 students. The instrument used consisted of 15 three-tier multiple-choice questions covering answers, reasoning, and the student's confidence levels. The validity and reliability of the instrument were tested through expert analysis and empirical testing using the Rasch model. Data collection was carried out using the three-tier multiple-choice test. After obtaining the students' responses, the answers were analyzed and categorized based on conceptual understanding levels: Understanding the Concept (UC), Negative Misconception (NM), Positive Misconception (PM), and Not Understanding the Concept (NUC). The results indicate that the average percentage of conceptual understanding was 29.05%, categorized as low; negative misconceptions were 23.10%, also categorized as low; postitive misconceptions were 10.24% categorized as very low; and not understanding the conceptions 37.62%, categorized as low. In conclusion, students of class XI B at SMA Negeri 2 Wonosari showed the lowest average level of conceptual understanding compared to those experiencing misconceptions or lacking scientific understanding of the concept.